2017
DOI: 10.1097/mao.0000000000001426
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Increase in Blood Levels of Otolin-1 in Humans

Abstract: Objective To test the hypothesis that age-related demineralization of otoconia will result in an age-related increase in blood levels of otoconia matrix protein, otolin-1. Study design Cross-sectional observational clinical trial. Setting Clinical research center. Patients Seventy-nine men and women ranging in age from 22 to 95 years old. Interventions Diagnostic. Main outcome measures Blood levels of otolin-1 in relation to age. Results Levels of otolin-1 of subjects divided into four age groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…As noted above, we have proposed the use of circulatory biomarkers toward better understanding of BPPV. We recently reported otolin-1 levels in healthy subjects as a function of age and noted a small but statistically significant age-related increase, consistent with degeneration of otoconia with age 18 . Now we hypothesize that if there is causal relationship between BPPV and low vitamin D levels, then there should be a relationship between otolin-1 and vitamin D levels in subjects without known vertigo.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…As noted above, we have proposed the use of circulatory biomarkers toward better understanding of BPPV. We recently reported otolin-1 levels in healthy subjects as a function of age and noted a small but statistically significant age-related increase, consistent with degeneration of otoconia with age 18 . Now we hypothesize that if there is causal relationship between BPPV and low vitamin D levels, then there should be a relationship between otolin-1 and vitamin D levels in subjects without known vertigo.…”
Section: Introductionmentioning
confidence: 56%
“…This study was approved by the Institutional Review Board at UConn Health (#12-188-2; 15-006-3). Details of subject recruitment and otolin-1 levels for our subjects were reported elsewhere 18 . Briefly, after receiving informed consent, blood samples were obtained from 20 young (20–30 years old), 20 middle-aged (50–65 years old), and 20 old (66–80 years old) individuals, as well as 19 subjects in the oldest-old group (81–95 years old) using services of the UConn Center on Aging Recruitment and Community Outreach Research Cores (http://health.uconn.edu/aging/research/research-cores/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It serves as a scaffolding protein that connects otoliths and otoconial core matrix proteins to the inner ear sensory epithelial and acellular gel matrix. Recently, studies reported that otolin-1 can be detected in serum and that its levels significantly increase with age, consistent with the age-related degeneration of otoconia (18)(19)(20). A preliminary study found that only one-third of patients with BPPV had higher serum otolin-1 values than those found in healthy controls because some of the enrolled BPPV patients were not in the acute stage (21).…”
Section: Introductionmentioning
confidence: 70%
“…Second, we did not measure other markers for bone metabolism and probable markers for otoconia. Recent reports suggested that an inner ear collagen named otolin-1 could be a serological biomarker for otoconia degeneration ( 39 41 ). In further studies, the correlations between otolin-1 and bone metabolism markers were explored.…”
Section: Discussionmentioning
confidence: 99%